EFEKTIVITAS Daphnia sp. YANG DIBERI PAKAN PELET TERHADAP PERTUMBUHAN LARVA IKAN SEMAH Tor douronensis (Valenciennes, 1842) - Dina Tri Madya Ningsih; Siti Hudaidah; Mas Tri Djoko Sunarno (Journal of Aquatropica Asia, 2020)
The semah fish (Tor douronensis) is an Indonesian endemic fish that has a long growth, which takes 4 years to grow from larvae to broodstock. This study aims know of Daphnia sp. pelet fed with effective doses to increase the growth of semah’s fish larvae. The study was conducted from March 25 to April 13, 2020 at the Instalasi Riset Plasma Nutfah, Cijeruk, Bogor, West Java. The experimental design used completely randomized design (CRD) 4 treatments and 3 replications, namely treatment A (Daphnia sp.+pelet feed 0 gr/ L), treatment B (Daphnia sp.+ pelet feed 1 gr / L), treatment C (Daphnia sp. + pelet feed 2 gr / L), treatment D (Daphnia sp. + pelet feed 3 gr / L). The larvae of 9 days in age were randomly stocked into 12 aquariums measuring 60x30x35 cm with a density of 50 fish/aquarium and fed in the form of Daphnia sp. enriched pelet feed according to the treatment of 50 ind/larvae by giving 3 times a day which is maintained for 20 days. The test parameters measured are absolute growth in length and weight, survival rate, and water quality. Based on the results of statistical analysis (Anova), the results showed that the treatment D gave the highest influence on the growth of semah’s fish larvae (P <0.05) with an absolute weight growth value of 85,3 mg, absolute length growth of 10.6 mm, and survival rate 99.33%.